Odin-OSIRIS stratospheric aerosol data product and SAGE III intercomparison - A. E. Bourassa (Atmospheric Chemistry and Physics, 2012)
The scattered sunlight measurements made by the Optical Spectrograph and InfraRed Imaging System (OSIRIS) on the Odin spacecraft are used to retrieve vertical profiles of stratospheric aerosol extinction at 750 nm. The recently released OSIRIS Version 5 data product contains the first publicly released stratospheric aerosol extinction retrievals, and these are now available for the entire Odin mission, which extends from the present day back to launch in 2001. A proof-of-concept study for the retrieval of stratospheric aerosol extinction from limb scatter measurements was previously published and the Version 5 data product retrievals are based on this work, but incorporate several important improvements to the algorithm. One of the primary changes is the use of a new retrieval vector that greatly improves the sensitivity to aerosol scattering by incorporating a forward modeled calculation of the radiance from a Rayleigh atmosphere. Additional improvements include a coupled retrieval of the effective albedo, a new method for normalization of the retrieval vector to improve signal-to-noise, and the use of an initial guess that is representative of very low background aerosol loading conditions, which allows for maximal retrieval range. Furthermore, the Version 5 data set is compared to Stratospheric Aerosol and Gas Experiment (SAGE) III 755 nm extinction profiles during the almost four years of mission overlap from 2002 to late 2005. The vertical structure in coincident profile measurements is well correlated and the statistics on a relatively large set of tight coincident measurements show agreement between the measurements from the two instruments to within approximately 10% throughout the 15 to 25 km altitude range, which covers the bulk of the stratospheric aerosol layer for the mid and high latitude cases studied here.